The killing. The complete second season [videorecording (DVD)] - Jenkins, Patty; Enos, Mireille, 1975-; Kinnaman, Joel, 1979-; Brown, Jamie Anne; Sexton, Brent; Campbell, William, 1959- (Twentieth Century Fox Home Entertainment, 2013)
Following the disappearance and murder of teenager Rosie Larsen, detectives search for suspects and try to solve the mystery of Rosie's death.